Scott Ortolano, ed. Popular Modernism and Its Legacies: From Pop Literature to Video Games. Bloomsbury Academic, 2018. - Lauren Rosales (Studies in 20th & 21st Century Literature, 2019)
Review of Scott Ortolano, ed. Popular Modernism and Its Legacies: From Pop Literature to Video Games. Bloomsbury Academic, 2018. 277 pp.
Keywords: modernism; postmodernism; popular modernism; Ortolano